(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2025)
This in the article “Uztransgaz” JSC objects construction, reconstruction to do and capital repair (QRK) works in the section economic efficiency increase methodology offer the study will be conducted in the first half of 2025. approved plan and current execution to the information relied on without expenses discipline, resource losses, energy expense and assets vital cyclical management complex evaluates. Traditional in approach efficiency general execution coefficient with is expressed; this and electricity energy, technological losses and some operational in paragraphs excess expenses does not attract enough " fines". The article "Capital repairs " integrated efficiency index (KTSI) It is released, it is the implementation of the QRK, the economy made funds, losses increase and excess expenses penalization does. Estimates 22.6% of total economical, 84% execution in the QRC, but technological 139% increase in losses shows correction the necessity.